Overview of the Full-scale Radiological Dispersal Device Field Trials. Issue 5 (May 2016) - Green, Anna Rae; Erhardt, Lorne; Lebel, Luke; Duke, M. John M.; Jones, Trevor; White, Dan; Quayle, Debora
Abstract : Abstract: In 2012, Defence Research and Development Canada, in partnership with a number of other Canadian and International organizations, led a series of three field trials designed to simulate a Radiological Dispersal Device (RDD). These trials, known as the Full-Scale RDD (FSRDD) Field Trials, involved the explosive dispersal of a short-lived radioactive tracer ( 140 La, t1/2 = 40.293 h). The FSRDD Field Trials required a significant effort in their planning, preparation, and execution to ensure that they were carried out in a safe, efficient manner and that the scientific goals of the trials were met. The discussion presented here details the planning and execution of the trials, outlines the relevant radiation safety aspects, provides a summary of the source term and atmospheric conditions for the three dispersal events, and provides an overview of the measurements that were made to track the plumes and deposition patterns.